Problems Experienced by Pre-School Teachers While Applying Assessment and Evaluation Methods - Furat, Ela; Sayin, H. Gonca Usta; Uluman, Muge (Elsevier BV, 2012)
AbstractAssessment and evaluation are inseparable and supplementary parts of education. When planning and implementation stages of education are examined, it is seen that assessment and evaluation are seen as important elements completing the process. In education, assessment and evaluation are used to determine the student's development level, readiness and learning difficulties. Assessment and evaluation methods, used in preschool, are especially used to monitor the student's level of development and to determine learning difficulties. Checklists, observation forms and portfolios are measurement tools frequently used. Since assessment and evaluation in this period are critical, it is quite important that pre-school teachers determine the problems while using assessment and evaluation methods. This research is a qualitative study trying to determine the problems of pre-school teachers in Ankara while using the assessment and evaluation methods.In this study, random sampling is used among probability sampling methods. In the research, data is collected by using half structured interview form prepared by researchers.Data is analyzed by using descriptive analysis method and is summarized according to themes determined by researchers.
Keywords: Presc Pre-school; Assessment; Evaluation; 4. Education